A Safety Checkpoint to Eliminate Cancer Risk of the Immune Evasive Cells Derived from Human Embryonic Stem Cells. (23rd February 2017) - He, Jingjin; Rong, Zhili; Fu, Xuemei; Xu, Yang
Abstract : Human embryonic stem cells (hESCs) hold great promise in the regenerative therapy of many currently untreatable human diseases. One of the key bottlenecks is the immune rejection of hESC-derived allografts by the recipient. To overcome this challenge, we have established new approaches to induce immune protection of hESC-derived allografts through the coexpression of immune suppressive molecules CTLA4-Ig and PD-L1 . However, this in turn raises a safety concern of cancer risk because these hESC-derived cells can evade immune surveillance. To address this safety concern, we developed a safety checkpoint so that the immune evasive hESC-derived cells in the graft can be effectively eliminated if any cellular transformation is detected. In this context, we knock-in the suicidal gene herpes simplex virus thymidine kinase ( HSVTK ) into the constitutive HPRT locus of CP hESCs (knock-in hESCs expressing CTLA4-Ig and PD-L1 ), denoted CPTK hESCs. Employing humanized mice (Hu-mice) reconstituted with human immune system, we demonstrated that the CPTK hESC-derived cells are protected from immune rejection. In addition, CPTK hESC-derived cells can be efficiently eliminated in vitro and in vivo with FDA approved TK -targeting drug ganciclovir. Therefore, this new safety checkpoint improves the feasibility to use the immune evasive hESC-derived cells for regenerative medicine.